Model Agile Scrum untuk Pengembangan Aplikasi Penerimaan Mahasiswa Baru - Meta Amalya Dewi; Muhammad Dimas Arya Syahputra (Teknik Informatika, 2022)
SCRUM is one of the agile developments with a focus on fast processes. Scrum's ability to quickly adapt to changes in accordance with the conditions of university which requires a New Student Admission application amid the current dynamics of the current condition in the midst of the Covid-19 pandemic that still sweeping the world so that almost all activities are carried out digitally, including the registration process and new student admissions. The agile scrum method used in developing new student applications is done by building an analysis that can help make it easier for prospective new students to carry out the registration process and make it easier for the admissions department to process new student data. The goal is to simplify data processing more optimally and effectively and the registration process is faster and easier. The final result of this research is an application for new student admissions with the features needed by users based on the product backlog and will become the backbone of the new student registration process at university.